Using intensive interaction and sensory integration : a handbook for those who support people with severe autistic spectrum disorder - Caldwell, Phoebe (Jessica Kingsley Publishers, 2008)
People with severe autism experience the sensory information they receive from the world completely differently to those not on the spectrum. They feel cut off and overwhelmed, and their behaviour can become very distressed. This handbook shows how we can engage with people who are non-verbal or semi-verbal and sometimes even those who have speech but lose the power to process it when they are in crisis. We can help them to make sense of the world. Intensive Interaction uses a person's own body language to make contact with them and Sensory Integration develops the capacity of an individual to.